MRI relaxometry: methods and applications - Carneiro,A. A. O. (2006)
Aspects of magnetic resonance relaxation measurements in human tissues are discussed. The influence of pulse sequences and parameters are compared and analyzed for different tissues. By controlling the acquisition parameters and data fitting the relaxation rate can be useful in several clinical situations. The influence of repetition and echo time, predicted in sequences of signal acquisition, on measurement of transversal relaxation time (T2) was evaluate using simulated MRI signal.